IMPROVING LOYALTY OF SCHOOL MANAGEMENT PERSONNEL THROUGH ORGANIZATIONAL COMMUNICATIONS APPROACH - Aini Safitri; Heri Rahmatsyah Putra (JURNAL TARBIYAH, 2021)
Teachers and employees are the driving force in the management of school institutions. Successfully managing a school depends on the flow of information from each level. Communication as a human need plays a crucial role in increasing the loyalty of school residents. Leadership communication to subordinates and vice versa and communication between members is also expected to create a harmonious working atmosphere. This study aims to determine the efforts to increase the loyalty of school personnel through an organizational communication approach by school principals by applying qualitative research methods that describe in-depth what was obtained from the informant. The study results indicate that the form of organizational communication in increasing the loyalty of school residents takes place vertically and horizontally. The principal communicates openly or directly at ceremonies and meetings and personally to teachers and employees in instructing all kinds of policies and providing encouragement to improve the performance of teachers and employees. Likewise, between teachers and employees, there is horizontal communication that creates a harmonious and pleasant work environment to increase employee loyalty and motivation.